KINERJA DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA PEKANBARU DALAM MELAKUKAN PEMERIKSAAN ANGKUTAN KOTA (UJI KIR) - AINUN NAZIFAH; ERNAWATI " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: Performance Dinas Perhubungan Komunikasi Dan Informatika City PekanbaruIn Conducting the Examination City Transport ( Test KIR).In order to do inspection citytransport in the case of test KIR. City transport is one of the transport that is widely used by thecommunity in the city pekanbaru. For that city must transit meet the three criteria in order forconvenience, security, and the feasibility of the road for passengers and other road users.Thereare several obstacles or constraints in conducting the examination city transport in the citypekanbaru still, among others, the number the city does not take care of the transport test KIR inaccordance with a predetermined time. In addition the city transport in pekanbaru his condition isvery poor, some of the vehicles were off due to old.Concept ofthe theoryisthat researchers useperformance. The performance consists of the responsiveness, responsibility and accountability.This researchused qualitative research methodswithstudyof descriptivedata.The results ofthisstudy indicatethat Dinas Perhubungan komunikasi dan informatika city pekanbaru in particularUPTD motor vehicle testing in conducting an examination test KIR it is not maximal, this is dueto the presence of the city transport already passed test KIR but still worrying situation, so maycause disquiet in the community.Keywords : Performance, Examination, Test KIR